Murine pancreatic ductal adenocarcinoma produced by in vitro transduction of polyoma middle T oncogene into the islets of Langerhans. - Yoshida, T. (1994)
Pancreatic islets isolated from juvenile but not aging adult mice, when infected with a retrovirus carrying polyomavirus middle T oncogene, produced cell lines, mPAC, with characteristics both of pancreatic ductal epithelium and neuroendocrine cells of the islets. Following three cycles of single cell cloning, mPAC cells consisted of two subtypes, a null cell, and a double-positive cell that co-expressed cytokeratin, a marker of ductal epithelium, and A2B5, a neuroendocrine ganglioside expressed in developing islet cells. Two islet cell genes, encoding somatostatin and pancreatic polypeptide, were transcribed at low levels in most mPAC clones, whereas the insulin and glucagon genes were not. Upon inoculation of mice, mPAC cells rapidly formed well-differentiated ductal adenocarcinomas that expressed cytokeratin but not the islet cell markers. The mPAC phenotype may result from a specific dedifferentiation of juvenile islet cells or ductal epithelium induced by middle T protein. Alternatively, mPAC cells may arise by transformation of a multipotential progenitor present within or in juxtaposition to juvenile islets. This cell type could therefore represent one of the targets in human cancers of the pancreatic duct. Moreover, signal transduction systems modulated by middle T, including src-related kinases, phosphatidylinositol kinase, and protein phosphatase 2A, may be involved in pancreatic carcinogenesis.